Optimization of Gear Manufacturing for Quality and Productivity - Thobadingoe Craven Phokane; KAPIL GUPTA; Cristina Anghel (Jurnal Optimasi Sistem Industri, 2022)
Multi-objective optimization in manufacturing can effectively be solved using Multicriteria decision-making (MCDM) techniques. This paper presents the implementation methodology of the Fuzzy-MOORA hybrid technique for multi-objective optimization in laser machining of stainless-steel gears. Further, simultaneous optimization of gear quality and process productivity have been reported. Four important laser parameters, i.e., laser power, cutting speed, focal position, and gas pressure, have varied during twenty-nine experiments to machine gears by a laser process. The quality of miniature gear was measured in terms of average surface roughness, mean roughness depth, and dimensional deviation. The productivity of the laser machining process was estimated via material removal rate. An optimum set of laser machining parameters obtained after Fuzzy-MOORA optimization is laser power 2000 W, cutting speed 3 m/min, focal position -2.5 mm, and gas pressure 16 bar. This work encourages researchers and scholars to make further attempts using such MCDM techniques to develop intelligent processes in industrial and manufacturing engineering.